2013
DOI: 10.1210/en.2013-1389
|View full text |Cite
|
Sign up to set email alerts
|

MK-2206, an AKT Inhibitor, Promotes Caspase-Independent Cell Death and Inhibits Leiomyoma Growth

Abstract: Uterine leiomyomas (ULs), benign tumors of the myometrium, are the number one indication for hysterectomies in the United States due to a lack of an effective alternative therapy. ULs show activation of the pro-survival AKT pathway compared with normal myometrium; however, substantial data directly linking AKT to UL cell survival are lacking. We hypothesized that AKT promotes UL cell survival and that it is a viable target for inhibiting UL growth. We used the investigational AKT inhibitor MK-2206, currently i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 50 publications
2
40
0
1
Order By: Relevance
“…The pathophysiology of myomas appears to involve Akt signaling, since myomas show higher levels of Akt than myometrium as well as aberrant Akt activation (identified by its phosphorylation, p-Akt) [7], which is essential for their growth and survival [64, 69]. Progesterone mediates rapid changes in myoma cells through a non-genomic PR signaling pathway [44] that phosphorylates Akt at Ser473 [13].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of myomas appears to involve Akt signaling, since myomas show higher levels of Akt than myometrium as well as aberrant Akt activation (identified by its phosphorylation, p-Akt) [7], which is essential for their growth and survival [64, 69]. Progesterone mediates rapid changes in myoma cells through a non-genomic PR signaling pathway [44] that phosphorylates Akt at Ser473 [13].…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that increased pAKT could be related to the overexpression of steroid receptors and receptor tyrosine kinases in leiomyomas. 47,48 Adenomyosis and endometriosis are both characterized by ectopic endometrial glands and stroma that have an invasive and hyperproliferative phenotype. Both entities often coexist and contribute to the same symptoms -infertility and pain symptoms -and the extent of both should be evaluated when deciding on a medical or surgical treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sefton and colleagues (118) demonstrated that Akt inhibition by MK-2206, an investigational drug currently in phase II trials, inhibits leiomyoma growth and induces cellular death. In addition, there is a published patent to use an mTOR inhibitor as a treatment of leiomyoma (119).…”
Section: Role Of Individual Growth Factors In Leiomyoma Pathobiologymentioning
confidence: 99%